Aromatic Hydroxylation of Indan by o-Xylene-Degrading Rhodococcus sp. Strain DK17 - Kim, Dockyu (American Society for Microbiology (ASM), 2010)

(untitled)
The metabolically versatile Rhodococcus sp. strain DK17 utilizes indan as a growth substrate via the o-xylene pathway. Metabolite and reverse transcription-PCR analyses indicate that o-xylene dioxygenase hydroxylates indan at the 4,5 position of the aromatic moiety to form cis-indan-4,5-dihydrodiol, which is dehydrogenated to 4,5-indandiol by a dehydrogenase. 4,5-Indandiol undergoes ring cleavage by a meta-cleavage dioxygenase.